Designing of 2-DOF PID control algorithm for magnetic levitation systems - Dinçer Maden; İrfan Yazıcı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, two degree of freedom (2-DOF)PID controllers are designed and compared to the conventional PID controller,which is compatible with the magnetic ball levitation system. This system is asubject of many control problems, because it has a open loop unstable andnonlinear second order structure. The system is modeled based on physicalparameters and its linearized around the appropriate equilibrium point viaTylor series expansion. The PID control parameters are determined by the rootplacement method which is a suitable method for the second order systems andthe same parameters are used for the 2-DOF PID. Since this proposed controlalgorithm has feedforward gain parameters, it is possible to improve thetransient state performance according to the traditional PID controller. Due tothe use of the conventional PID controller, there are some zeros in thetransfer function of the system. It can be seen that proposed technique couldprevent the overshoots caused by these zeros.